2018
DOI: 10.2340/00015555-2895
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Combined Treatment of Surgery and Adjuvant Radiotherapy in Merkel Cell Carcinoma

Abstract: In recent analyses of Merkel cell carcinoma, prognosis is poor even in stages I and II. We performed a monocentric retrospective study of 37 consecutive cases with Merkel cell carcinoma stage I to III treated with a combination of surgery and adjuvant radiation to evaluate progression-free and overall survival. The median primary tumour diameter was 17.9 mm. Cases consisted of 31 primary tumours, of which 13 had negative sentinel lymph node biopsy (IA n = 10 and IIA n = 3) and 18 no sentinel lymph node biopsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…MCC, as other neuroendocrine carcinomas, is responsive to RT and adjuvant RT is advised in the NCCN guidelines in local disease except for small low risk tumours (NCCN). Reports on the survival benefit of adjuvant RT are, however, controversial [11,[37][38][39][40]. To date, the only randomized controlled study on adjuvant RT was conducted by Jouary et al [41] on stage I MCC patients, in which RT to the tumour bed resulted in a significant decrease in local recurrence, but no significant improvement in overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…MCC, as other neuroendocrine carcinomas, is responsive to RT and adjuvant RT is advised in the NCCN guidelines in local disease except for small low risk tumours (NCCN). Reports on the survival benefit of adjuvant RT are, however, controversial [11,[37][38][39][40]. To date, the only randomized controlled study on adjuvant RT was conducted by Jouary et al [41] on stage I MCC patients, in which RT to the tumour bed resulted in a significant decrease in local recurrence, but no significant improvement in overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Longer OS was observed for SUR + adjRT versus surgery alone in a study conducted in patients with stage I, II and III disease [16]. Because of the discrepancy between the effects of SUR + adjRT versus surgery in various regions of the body, systemic therapies could also be considered if SUR + adjRT is impossible due to RT contraindication [25]. The diversity of treatments suggests that no clear pathway or standard of care exists for patients with early stage MCC; these findings can support and complement the information already presented by the NCCN guidelines for stage I-III MCC.…”
Section: Discussionmentioning
confidence: 99%
“…One publication showed that patients with stage I, II and III MCC treated with SUR + adjRT had a PFS rate of 86.5% at 5 years. The mean PFS was 155.1 months (CI: 122.4-187.8 months; standard error, 16.7 months) [25].…”
Section: Progression-free Survivalmentioning
confidence: 98%
See 2 more Smart Citations